Ocean science, data, and services for the UN 2030 Sustainable Development Goals. (November 2020) - von Schuckmann, Karina; Holland, Elisabeth; Haugan, Peter; Thomson, Peter
Graphical abstract: Relating the Sustainable Development Goal (SDG) 14 for Ocean and Life Below Water to the 16 remaining SDGs in the UN 2030 sustainable development agenda. A holistic approach that embraces sustainable Ocean stewardship informed by best available science, data and services to support society and the economy is required to create the 'Future We Want'. The UN Decade of Ocean Science for Sustainable Development is an essential foundation to achieve this objective. Image 1